Studi Komparatif Nikah Online Menurut Mazhab Syafi’iyah dan Mazhab Hanafiyah - Erika nurrohmah Shobaikah; Yandi Maryandi; Fahmi Fatwa Rosyadi (Bandung Conference Series: Islamic Family Law, 2022)
Abstract. Marriage is a very sacred legal act in which in marriage there is a great agreement with Allah SWT between a man and a woman to build a sakinah, mawaddah, warahmah household, and between the two there is no lineage or mahram relationship. In Islamic law, marriage is declared valid if it is carried out according to religious teachings and the marriage contract complies with sharia. The purpose of the study was to find out how the law of marriage online according to the Shafi'iyah and Hanafi'iyah schools of thought. In this study, the research method used a qualitative approach and data collection was carried out by means of a literature study. The conclusion according to Islamic law is that marriage will be declared valid if the pillars of marriage and the conditions of marriage are met. According to the Syafi'iyah school, the marriage contract must be carried out continuously, which is after the marriage guardian pronounces the consent and the prospective husband pronounces Kabul and must be in one assembly while the Hanafi'iyah school allows for different places or majlis. Abstrak. Pernikahan merupakan suatu perbuatan hukum yang sangat sakral yang mana dalam pernikahan terdapat perjanjian yang agung terhadap Allah SWT antara laki-laki dan perempuan untuk membina rumah tangga yang sakinah mawadah warahmah.dan di antara keduanya tidak memliki nasab atau hubungan mahram. Dalam syartiat islam pernikahan dinyatakan sah apabila dilaksanak menurut ajaran agama dan akad nikahnya memnuhi syara. Tujuan penelitian untuk mengetahui bagaimana hukum pernikahan secara daring menurut mazhab syafi’iyah dan mazhab hanafi’iyah . dalam penelitian ini metedo penelitian menggunakan pendekatan kualitatif dan pengumpulan data di lakukan dengan studi pustaka. Hasil kesimpulan menurut hukum islam bahwa pernikahan akan di nyatakan sah apabila rukun nikah dan syarat nikah nya terpenuhi. Menurut mazhab Syafi’iyah akad nikah harus dilakukan secara kesinambungan yang mana setelah wali nikah mengucapkan ijab dan calon suami mengucapkan Kabul dan harus dalam satu majelis sedangkan mazhab Hanafi’iyah memperbolehkan adanya perbedaan tempat atau majlis.